Evaluation of Hematological Parameters In Patients With Hepatitis B virus - Al-mammory, Ginan Kareem; Flyyih, Najat Mohammed; Deli, Doaa Abd Alzahra (Medical Science Journal for Advance Research, 2024)
Background: Hepatitis refers to an inflammation of the liver and caused by numerous factors, such as alcohol, obesity also can be occurred by viruses such as hepatitis viruses (A,B,C,D). To determine of some haematology parameters of hepatitis B-virus in patients is the purpose of this study. All data was collected from 100 persons, divided into two groups: patients and control. The medical information about the patients includes age, gender and duration in hospital. The HbsAg for all participants persons is detecting by using the enzymes-linked immune sorbent assay (ELISA) and divided the positive group into an acute stage and chronic stage by special doctors. All parameters indicate by complete blood count in Haematology Analyzer, including white blood cells (WBC), lymphocyte cells (LYM), red blood cells (RBC) hemoglobin (HGB), platelets (PLT) and mean platelet volume (MPV) . The Results show patients with hepatitis B-virus infection show changing in the levels of parameters that using in this study compared with healthy controls.